Johann Georg Zimmermann's internalised republicanism - Tarkka, Laura (Taylor & Francis, 2025)
This article draws attention to the transformation of the Swiss physician Johann Georg Zimmermann's (1728-1795) work on national pride. First published as Von dem Nationalstolze in 1758, this work attracted trans-European interest and consequently appeared in substantially revised editions in 1760 and 1768. One notable addition in the new editions was a chapter on national pride felt by the subjects of monarchies, which could be taken as indicating a monarchist turn in Zimmermann's thinking. However, as the article contends, Zimmermann's work can be read not only as a treatise making claims about the national pride of various countries but also as a text which, in so doing, attempted to encourage liberty and patriotic virtue in different societies. As such, it can be interpreted as representing a variation of republicanism that focussed solely on reforming the thinking of individuals. This argument is based on an analysis of the evolution of Zimmermann's work, his correspondence, contemporary reviews, and a set of unpublished draft prefaces. As this evidence indicates, Zimmermann aspired to promote a republican attitude wherever his readers were situated. However, appreciating this 'internalised republicanism' requires that his writing is examined as a process involving the reactions of his expanding audience.